Consumption-Based Asset Pricing with a Reference Level: New Evidence from the Cross-Section of Stock Returns - Joachim G. Grammig; Andreas Schrimpf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper presents an empirical evaluation of recently proposed asset pricing models which extend the standard preference specification by a reference level of consumption. The novelty is that we use a broad cross-section of test assets, which provides a level playing field for a comparison to well-established benchmark models. We also motivate a specification that accounts for the return on human capital as a determinant of the reference level. We find that this extension does a good job in explaining the cross-sectional variation in average returns across the 25 Fama- French portfolios with pricing errors close to those of Lettau/Ludvigson's celebrated scaled factor models.
More recent version: http://hdl.handle.net/10419/24703
Keywords: G12; 330; Consumption-based Asset Pricing; Cross-Section of Stock Returns; Reference Level; Börsenkurs; Kapitalertrag; Capital Asset Pricing Model; Schätzung; Theorie; Welt